Correlation between Oxidative Stress with Cartilage Thickness and Catalase Activity in Osteoarthritis Model Rat after MSC-WJ Treatment - Endrinaldi Endrinaldi; Rauza Sukma Rita; Tofrizal Tofrizal; Sisca Dwi Yarni (Majalah Kedokteran Andalas, 2021)
Objective: This study was conducted to investigate the involvement of oxidative damage in rat model of osteoarthritis treated with Mesenchymal Stem Cell Wharton Jelly and to elucidate whether oxidative stress indicators correlate with cartilage damage and catalase activity. Methods: This research is an experimental research with Posttest-Only Control Group Design. The sample consisted of 30 OA rat divided into 5 groups. Group I was the OA rat control group, group II was the OA rat group after 4 weeks, group III was the OA rat group after 8 weeks, group IV was the OA rat group after 4 weeks of treatment with MSC-WJ and group V is the OA rat group after 8 weeks treated with MSC-WJ. Malondialdehyde were measured by Ohkawa method, Cartilage Thickness were measured by using the Betaview program and catalase activity were measured by modification of Shinha.Results: The results showed that the analysis of the Correlation between MDA with Cartilage Thickness (r= – 0.665) and CAT activity (r= – 0.666) in osteoarthritis Model Rat after Mesenchymal Stem Cell Wharton’s Jelly Treatment.Conclusion: This study demonstrated a strong negative correlation between oxidative stress and knee cartilage thickness and catalase activity of MSC-WJ treated OA rats.